The Effect of Social Media on MSME Performance Through Innovation Capability - Cahyono, Tomy Dwi; Sunardi, Sunardi; Supriadi, Bambang (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
Social media has become an essential tool for micro, small, and medium enterprises (UMKM) to improve business performance. This study aims to examine the effect of social media on MSME performance through innovation capability as a mediating variable. The research was conducted quantitatively using Partial Least Square Structural Equation Modeling (PLS-SEM), with data collected from 100 UMKM actors in Sumbawa Regency who actively use social media for business purposes. The results show that social media significantly influences innovation capability, and innovation capability significantly affects MSME performance. Moreover, the indirect effect of social media on MSME performance through innovation capability is also significant, indicating that innovation plays a crucial role in translating digital engagement into business success. These findings suggest that merely using social media is not enough; UMKM must leverage it to drive innovation in products, services, and market strategies to achieve sustainable growth.